2015
DOI: 10.1111/jop.12377
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical expression of alpha‐smooth muscle actin and glucocorticoid and calcitonin receptors in central giant‐cell lesions

Abstract: Myofibroblasts are important components of CGCLs, stromal cells and alpha-smooth muscle. Actin immunoexpression was associated with root and cortical bone resorption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…This result is in agreement with the previous studies. [ 17 ] Thus, myofibroblasts are important components of stromal cells in central giant cell lesions and alpha-smooth muscle actin immunoexpression was associated with features of local aggressiveness such as root resorption and cortical bone involvement. [ 15 18 ] Moreover, the pattern of distribution of these mononuclear myofibroblastic cells around the abnormal vessel spaces suggested that these cells might play a role in generating newly formed blood vessels and spaces.…”
Section: Discussionmentioning
confidence: 99%
“…This result is in agreement with the previous studies. [ 17 ] Thus, myofibroblasts are important components of stromal cells in central giant cell lesions and alpha-smooth muscle actin immunoexpression was associated with features of local aggressiveness such as root resorption and cortical bone involvement. [ 15 18 ] Moreover, the pattern of distribution of these mononuclear myofibroblastic cells around the abnormal vessel spaces suggested that these cells might play a role in generating newly formed blood vessels and spaces.…”
Section: Discussionmentioning
confidence: 99%